2019
DOI: 10.1016/j.rmed.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a homeopathic medication on upper respiratory tract infections in COPD patients: Results of an observational, prospective study (EPOXILO)

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a progressive lung disorder in which airflow is obstructed. Viral or bacterial upper respiratory tract infections (URTIs) may lead to exacerbations. Homeopathic medication administration to COPD patients during the influenza-exposure period may help to reduce the frequency of common URTIs. Methods: This prospective, observational, multicenter study was carried out in Cantabria, Spain. Patients with COPD were divided into two groups: group 1 received c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 46 publications
0
31
0
3
Order By: Relevance
“…Ці показники становили 1,9 % проти 13,8 % відповідно для пацієнтів, які мали ≥ 3 інфекції верхніх дихальних шляхів. Середня тривалість симптомів за 1 епізод інфекцій верхніх дихальних шляхів також була значно меншою в пацієнтів основної групи (3,57 проти 5,22 дня відповідно; на 1,65 дня менше; р = 0,012) [21].…”
Section: оöилоêоêöінумunclassified
See 1 more Smart Citation
“…Ці показники становили 1,9 % проти 13,8 % відповідно для пацієнтів, які мали ≥ 3 інфекції верхніх дихальних шляхів. Середня тривалість симптомів за 1 епізод інфекцій верхніх дихальних шляхів також була значно меншою в пацієнтів основної групи (3,57 проти 5,22 дня відповідно; на 1,65 дня менше; р = 0,012) [21].…”
Section: оöилоêоêöінумunclassified
“…Цей гомеопатичний препарат можна застосовувати як у дорослих і дітей, яким не проводилось щеплення з різних причин, так і в пацієнтів, які отримали щеплення проти грипу, особливо у хворих на ХОЗЛ [21]. Хоча Оцилококцінум не замінює вакцинацію проти сезонних штамів, але розширює і доповнює можливості профілактики сезонних ГРВІ, оскільки доведено сприяє тимчасовій активізації противірусної ланки імунітету, що було зазначено вище.…”
Section: оöилоêоêöінумunclassified
“…Out of 11 prospective studies, 6 studies compared homeopathy to conventional treatment (CT). Conde Diez et al, 44 Danno et al 45 and Vincent et al 46 (219, 573 and 461 patients respectively) comparing homeopathy with conventional treatment in influenza/ILI found homeopathy widely accepted and beneficial. The other three studies on URTIs comparing same by Grimaldi-Bensouda et al, 47 Haidvogl et al 48 and Riley et al 49 (518, 1577 and 500 patients, respectively) suggested homeopathy was non-inferior to CT.…”
Section: Comparative Cohort Studiesmentioning
confidence: 99%
“…A recent retrospective observational study conducted in Spain demonstrated that patients with COPD treated with Oscillococcinum (a patented homeopathic medicine (Boiron SA, Messimy, France), authorized since 1944 and sold in over 80 countries around the world) had an important reduction in mean number and duration of URTIs and COPD exacerbations compared with untreated patients. 12 Oscillococcinum is traditionally used in the relief of flu-like symptoms such as fever, headache, chills and body aches. Several studies have shown the efficacy of this medication in the treatment of influenza-like illness and URTIs.…”
Section: Introductionmentioning
confidence: 99%